Building Religious Harmony Among Young Children: Experience from Indonesian Elementary School - Syafar, Djunawir (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2019)
This article is a study of the harmonization of Islam, Christianity, and Buddhism in SD Negeri (State Elementary School) 46 Hulontalangi, Gorontalo City. The school plays important roles because it is the first state school in Gorontalo City that develops and implements the concepts of religious harmony and pluralism in a school environment. This research is a qualitative study which uses three data collection methods, namely: (1) observation, (2) in-depth interviews, (3) documentation. The findings show that the implementation of religious harmony is manifested in religious, social, and cultural cooperation. The cooperation has become a habit that affects the outlook and actions of all school members in their daily lives. The habit is inseparable from the role of teachers, parents, students, and all school residents who become teachers and learners from their environment. It results in harmony cooperation, namely cooperation that is not only in the form of ideas and words but also affects the social environment. Thus, what has been implemented at this institution can be an alternative solution for schools or other institutions on how religious pluralism can be facilitated and placed in the right position and needs.